(untitled) (Polis (Santiago), 2021)
The aim of this article is to investigate the social representations of childhood in a group of women interveners in two dimensions: 1) migrant childhood, like actor that demands intervention in a pandemic; and 2) the experience of childhood of the women is analyzed, from a biographical approach. A qualitative methodology was used via a self-administered questionnaire in electronic format, that evidenced the use of so-called inclusive language. A content and intersectional analyses were applied. The sample consisted of twenty-four professional, technical and volunteer women of various nationalities who work in NGOs in regions of the northern and central zone of Chile. The article concludes that the intervening women identify a representation of migrant children as subjects defined by what they are lacking, in a situation of helplessness and rights violations that affect their quality of life, even more so in the context of a health crisis and scarce institutional response. As a counterpoint, the childhood experience of the intervening women emerges as a diverse representation, where the protagonism of an acting subject who speaks in the first person is visible, even in adversity. Thus, the intersectional analysis of the representation -or representations- of childhood -or childhoods- becomes an input that nourishes their praxis.